The Impacts of Geographical Indication Registration on Career Sustainability of Agriculturists: Study the Case of Siam Ruby Pomelo - Pangfoo, Pimonkorn; Khongkaew, Thaweephorn; Dangngam, Taragade; Mudlem, Fareeda; Tongroot, Chadarat (Asia Social Issues, 2020)
The research aims to study the impacts of Geographical Indication (GI) Registration on career sustainability of agriculturists in the case of Siam Ruby Pomelo (Pak Phanang) and to provide suggestions for production process development after the process of GI Registration. In practice, the study examines the effects on career sustainability of agriculturists in the community and employs the data on the impact of Geographical Indication Registration for Siam Ruby Pomelo (Pak Phanang) as a guideline for developing local processes for pomelo growers. The results of study indicate that GI Registration and GI symbol application have effects on career sustainability of the majority of the research samples, mostly on income or financial status overall. Especially, after GI symbol application, there are more sales opportunities and channels of distributing products. Moreover, the study shows that GI symbol application plays an immense role in consumer confidence. However, no evidence shows significant disparity on the life quality, nor social life of the research samples when compared to their financial status.